Women's perspective on the accessibility to cervical cancer screening: a review - B., Anisah (Community Health Society Malaysia (CHSM), 2016)
Women’s health behaviour pertaining to cervical cancer screening is a complex inter- and intra-relationship between concerns on health matters and other internal and external influences. Women’s decision to seek preventive health care such as cervical cancer screening is being made complicated by women’s status in the society. This review looks into women’s perspectives in seven areas of influences namely, knowledge; psychosocial; gender roles and norms; accessibility; beliefs, attitudes and perceptions; health services; and, language and communication. These influences are interlinked with each other and they function simultaneously. This review also showed that knowledge alone is inadequate to enable women to seek cervical cancer screening. Other factors interplay to hinder women from attending screening.